Hubungan Antara Pola Pemberian Makan, Riwayat Penyakit dan Riwayat ASI Eksklusif dengan Status Gizi Pada Balita di Kelurahan Curug Manis, Serang - Syavika Ismi Aulia; Delly Arfa Syukrowardi (STIKes Karsa Husada Garut, 2019)
The increasing number of malnutrition children under five years is treated health status of community in developing countries including Indonesia. The purpose of this study was to determine the relationship between dietary habits, disease history, and history of exclusive breastfeeding with nutritional status in children under five in Curug Manis Village at working area of Curug Community Health Center in 2019